Ectoparasites and Water Quality Management on Silver Pompano in Rearing Floating Net Cages at the Center for Mariculture Fisheries (BBPBL) Lampung - Adella, Catlya Tasya; Maulidah, Aulia; Kismiyati, Kismiyati (Juvenil, 2025)
ABSTRACTThe production value of silver pompano has been increasing annually, with strong market demand both locally and internationally. One significant issue in silver pompano aquaculture is infectious diseases caused by parasites. Water quality, being a critical component of the fish's environment, plays a crucial role in disease occurrence, necessitating effective management practices. This study was conducted at the Center for Mariculture Fisheries (BBPBL) Lampung from July 11 to August 31, 2022, aiming to identify the species, intensity, and methods for examining ectoparasites on silver pompano in floating net cages and to assess water quality management practices that can mitigate the proliferation of parasitic diseases. The methodology employed included direct examination and observation. Ectoparasite assessments at BBPBL Lampung involved scraping the surface of the fish body and mounting the fish gills. The identified ectoparasites in the floating net cages of silver pompano were Pyragraphorus hollisae, Benedenia seriolae, and Neobenedenia girellae. Water quality management in the floating net cages is routinely monitored on a weekly basis.Keywords: BBPBL Lampung, Ectoparasites, Silver Pompano, and Water Quality.